OS4.6 Does radiation target volume affect health-related quality of life in patients with low grade glioma on the short-term? - a secondary analysis of the EORTC 22033–26033 trial. (19th September 2018) - Seidel, C; Dirven, L; Rejneveld, J C; Coens, C; Taphoorn, M J B; Gorlia, T; Tzuk-Shina, T; Back, M; Stupp, R; Baumert, B
Abstract: Background: It is currently unknown whether increasing radiotherapy volumes have a negative impact on the health-related quality of life (HRQoL) of low-grade glioma (LGG) patients on the short-term. The aim of this study was to examine if the size of the target volume is independently associated with HRQoL. Material and Methods: Patients treated with radiotherapy in the European Organisation for Research and Treatment of Cancer (EORTC) 22033–26033 study, and who completed a baseline HRQoL form, were included. This phase 3 trial of radiotherapy vs. temozolomide chemotherapy in high-risk LGG requiring treatment did not show a progression free survival difference. HRQoL was measured at baseline and every 3 months thereafter until progression, using the EORTC QLQ-C30 core questionnaire and QLQ-BN20 brain module. Associations between radiation volumes and (changes in) four preselected HRQoL scales (global health status, cognitive and social functioning, and fatigue) were determined. Also, it was determined if radiation volumes were independently associated with a change in HRQoL over time. Results: A total of 195 out of the 240 patients randomized to radiotherapy (81.3%) were included in this analysis. The brain volume receiving radiotherapy was not associated with (changes in) HRQoL during the first 24 months after radiotherapy. Over time, radiation volumes were also not independently associated with HRQoL. Although treatment with radiotherapy resulted in worse functioning, and more fatigue three months after treatment, pre-treatment levels were reached thereafter and maintained during further follow-up. Particularly the occurrence of tumour progression was found to be associated with clinically relevant worse social functioning (Beta: -13.7, 95% CI:-19.5 to -7.9), and more fatigue (Beta: 13.2, 95% CI:7.8–18.5) during 24 months follow-up. Conclusion: The volume of brain receiving focal radiotherapy does not seem to be an important determinant for the level of HRQoL in high-risk LGG patients on the short-term. From this point of view, safety margins do not need to be reconsidered. However, the impact of radiation volumes on long-term HRQoL, as well as neurocognitive functioning, remains to be investigated.